PENGARUH SUKU BUNGA KREDIT, INFLASI DAN NILAI TUKAR TERHADAP PENYALURAN KREDIT PADA BANK PEMBANGUNAN DAERAH (BPD) SE PULAU JAWA - Iwan Yunanto, 10.05.51.0133 (Students Journal of Economic and Management, 2015)
This study examines the effect of Influence Lending Rates, Inflation and Exchange Rate Against Lending At the Regional Development Bank (BPD) in Java. This research was conducted through the collection of secondary data obtained from Bank Indonesia and the Central Bureau of Statistics with adequate sample. The results of the study provide evidence that factors in lending rates and the exchange rate affects lending policies in the Regional Development Bank (BPD) in Java. Keyword :Â Â Â Lending Rates, Inflation, Exchange Rate, Lending